2013
DOI: 10.5433/1679-0359.2013v34n6p2575
|View full text |Cite
|
Sign up to set email alerts
|

Substratos com compostos de adubos verdes e biofertilizante via foliar na formação de mudas de maracujazeiro-amarelo

Abstract: ; Ronaldo do Nascimento 4 ResumoSubstratos e adubações são fundamentais para a produção de mudas, que bem nutridas produzem precocemente e resistem melhor a estresses. Estercos são muito utilizados em substratos não industrializados, com bons resultados para as mudas, mas seu custo tem se elevado. Outros resíduos podem ser utilizados para nutrir as plantas, tanto via substrato quanto via adubação foliar. O objetivo do trabalho foi avaliar substratos elaborados com compostos orgânicos de adubos verdes e o uso d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
0
9
1
8
Order By: Relevance
“…Cavalcante et al (2016b) used the organic composite in passion fruit seedlings. The values observed for the nitrogen contents are higher than those of the other plant species studied, as described by Barros et al (2013), who worked with different organic substrates in yellow passion fruit seedlings (Passiflora edulis Sims f. Flavicarpa Degene) and showed that the nitrogen accumulation was better in the substrate composed of soil and tanned bovine manure. Reis et al (2015) obtained a value of 16.79 g kg -1 working with Dilodendron bipinnatum Radkl (Sapindaceae); whereas Antunes et al (2016) found values varying between 9.73 and 12.44 g kg -1 using vermicompostos of different agroindustrial residues in black acacia (Acacia mearnsii Wild).…”
Section: Discussionmentioning
confidence: 63%
“…Cavalcante et al (2016b) used the organic composite in passion fruit seedlings. The values observed for the nitrogen contents are higher than those of the other plant species studied, as described by Barros et al (2013), who worked with different organic substrates in yellow passion fruit seedlings (Passiflora edulis Sims f. Flavicarpa Degene) and showed that the nitrogen accumulation was better in the substrate composed of soil and tanned bovine manure. Reis et al (2015) obtained a value of 16.79 g kg -1 working with Dilodendron bipinnatum Radkl (Sapindaceae); whereas Antunes et al (2016) found values varying between 9.73 and 12.44 g kg -1 using vermicompostos of different agroindustrial residues in black acacia (Acacia mearnsii Wild).…”
Section: Discussionmentioning
confidence: 63%
“…Barros et al (2013) found significance in the dry root mass when evaluating different substrates made with compounds of green manure and application of foliar biofertilizers in seedlings of yellow passion fruit, however, the substrate with manure, provided dry mass increase and should be the best fertility conditions provided to the substrate. Cruz et al (2008) observed that the use of swine wastewater in irrigation of sour passion fruit seedlings provided increase in the amount of dry matter of seedlings, supplying the nutritional demand of seedlings without the supply of commercial fertilizers.…”
Section: Resultsmentioning
confidence: 97%
“…Cavalcante et al (2010) in guava plants observed that treatment with cattle manure was superior to the leaf area and length of the guava root, with a maximum of 167.5 cm² value for leaf area and 29 cm long root. Barros et al (2013) in passion fruit, obtained the best results for leaf area (966.3 cm²) and root length (17 cm) with substrates composed of hardened soil + cattle manure. In guava rootstocks treated with manure proportions, there was increasing linear behavior due to the increase of manure ratios for the leaf area to 90 ( Figure 8A) and 120 DAS ( Figure 8B), representing increases of 0,0349 cm² to 90 DAS for each unit increase in cattle manure proportions.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2015) observed that the proportion of 37.25% of manure gave the highest root dry mass values (3.49 g). Barros et al (2013) in passionflower, achieved the best results (1.32 g) to root dry mass with substrates composed of cattle manure + hardened soil. Cavalcante et al (2010) studied saline water and liquid manure in the formation of guava plants grow paluma observed that plants treated with liquid manure bovine had damage to a lesser extent in the treatments with organic input.…”
Section: Resultsmentioning
confidence: 99%